American College of Rheumatology/Spondylitis Association of America/Spondyloarthritis Research and Treatment Network 2015 Recommendations for the Treatment of Ankylosing Spondylitis and Nonradiographic Axial Spondyloarthritis. Issue 2 (24th September 2015) - Ward, Michael M.; Deodhar, Atul; Akl, Elie A.; Lui, Andrew; Ermann, Joerg; Gensler, Lianne S.; Smith, Judith A.; Borenstein, David; Hiratzka, Jayme; Weiss, Pamela F.; Inman, Robert D.; Majithia, Vikas; et al.
Abstract : Objective: To provide evidence‐based recommendations for the treatment of patients with ankylosing spondylitis (AS) and nonradiographic axial spondyloarthritis (SpA). Methods: A core group led the development of the recommendations, starting with the treatment questions. A literature review group conducted systematic literature reviews of studies that addressed 57 specific treatment questions, based on searches conducted in OVID Medline (1946–2014), PubMed (1966–2014), and the Cochrane Library. We assessed the quality of evidence using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) method. A separate voting group reviewed the evidence and voted on recommendations for each question using the GRADE framework. Results: In patients with active AS, the strong recommendations included use of nonsteroidal antiinflammatory drugs (NSAIDs), use of tumor necrosis factor inhibitors (TNFi) when activity persists despite NSAID treatment, not to use systemic glucocorticoids, use of physical therapy, and use of hip arthroplasty for patients with advanced hip arthritis. Among the conditional recommendations was that no particular TNFi was preferred except in patients with concomitant inflammatory bowel disease or recurrent iritis, in whom TNFi monoclonal antibodies should be used. In patients with active nonradiographic axial SpA despite treatment with NSAIDs, we conditionally recommend treatment with TNFi. Other recommendations for patients with nonradiographic axial SpA were based on indirect evidence and were the same as for patients with AS. Conclusion: These recommendations provide guidance for the management of common clinical questions in AS and nonradiographic axial SpA. Additional research on optimal medication management over time, disease monitoring, and preventive care is needed to help establish best practices in these areas.